6(x-3)=-3x-54

Simple and best practice solution for 6(x-3)=-3x-54 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x-3)=-3x-54 equation:


Simplifying
6(x + -3) = -3x + -54

Reorder the terms:
6(-3 + x) = -3x + -54
(-3 * 6 + x * 6) = -3x + -54
(-18 + 6x) = -3x + -54

Reorder the terms:
-18 + 6x = -54 + -3x

Solving
-18 + 6x = -54 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-18 + 6x + 3x = -54 + -3x + 3x

Combine like terms: 6x + 3x = 9x
-18 + 9x = -54 + -3x + 3x

Combine like terms: -3x + 3x = 0
-18 + 9x = -54 + 0
-18 + 9x = -54

Add '18' to each side of the equation.
-18 + 18 + 9x = -54 + 18

Combine like terms: -18 + 18 = 0
0 + 9x = -54 + 18
9x = -54 + 18

Combine like terms: -54 + 18 = -36
9x = -36

Divide each side by '9'.
x = -4

Simplifying
x = -4

See similar equations:

| f(x)=9x^2+54x+71 | | (5g^3+2)-(6g+6)-(4g^3-3g)=0 | | (7b^4-4)-(7b^3-5)+(4b^4-3b^3)=0 | | secx+cosx=0 | | 2r^2-10r-48=0 | | 3(9n+5)+8(10n-9)=y | | 4(3x-1)+9(-5x+2)=y | | 9(6a-10)+2(-6a+8)=y | | 6(4k-5)-4k=y | | -9(2-10a)+8a=y | | 3(1+8m)=y | | 4(9+4x)=y | | f(x)=2x^2-36x+169 | | 6x+43=300 | | -6(8+x)-7=y | | 7(-6m-8)+9m=y | | 10(-2b+8)+2=y | | 10(1-6v)=y | | 10(1-6v)=y | | 7(x*6)+y=119 | | -6(b-2)=y | | 5x^3=8 | | x^4+x^3+x+4=0 | | -7(10p-7)=y | | -4p-2p=y | | 2a-10a=y | | 1-8n-9n=y | | x*7+45=80 | | 2x+y=74 | | 6y-18y=6 | | 6x+11=-31 | | 3x=10-9 |

Equations solver categories